Alkali-free liquid flocculant for nano-sol combined spray coating and preparation method and application thereof
Through the use of alkali-free liquid flocculants, the safety hazards and environmental protection problems of strong alkali flocculants in blast furnace iron smelting are solved, the adhesion and mechanical properties of spray coatings are improved, and the efficiency and safety of blast furnace lining repair is improved. sex.
Patent Information
- Application Number
- CN202411425673.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing strong alkali flocculants have safety hazards, environmental protection problems and low spray efficiency in the blast furnace ironmaking process, making it difficult to effectively solve the damage to the blast furnace lining and cooling wall.
Using alkali-free liquid flocculant composed of magnesium chloride, magnesium sulfate, lithium chloride and thickener, nanosol combined spray coating is prepared through a stirring device to promote silica sol gelation and improve the early strength and adhesion of spray coating. .
The safety and environmental protection of alkali-free liquid flocculants are achieved, the rebound rate of spray coatings is reduced, the spray efficiency and the mechanical strength of the material are improved, and it is suitable for blast furnace lining repair.
Smart Images

Figure CN118909480B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of refractory materials, and in particular to an alkali-free liquid flocculant for a nano-sol combined spray coating, and a preparation method and application thereof. Background Art
[0002] Blast furnace ironmaking is the mainstream ironmaking process in the world, and its pig iron production accounts for more than 90% of the world's total pig iron production. As a smelting equipment for long-term, continuous, and high-temperature production, the blast furnace will be affected by high temperature, furnace wear, chemical corrosion of slag and alkali metals, molten iron circulation, thermal stress and other factors during its production and operation, which will cause damage to the lining and cooling wall of the blast furnace. Wet spray repair has been widely used in the repair of blast furnace linings in the world due to its advantages such as fast maintenance speed, good integrity of the repaired lining, and more conducive to furnace operation. Nanosol combined with wet spray coating has become the main spray product for blast furnace repair in recent years due to its excellent medium and high temperature strength performance. Flocculant is the core material for the transformation of wet spray coating from a flowing state to a plastic state. It has a direct impact on the adhesion, rebound rate, spray efficiency and material hardening of the sprayed material. Compared with traditional strong alkaline flocculants, alkali-free flocculants have gradually become a hot spot and direction of market research due to their advantages such as being able to avoid burn accidents and being more environmentally friendly. Summary of the invention
[0003] In order to solve the many problems existing in the existing strong alkaline flocculants, the purpose of the present invention is to provide an alkali-free liquid flocculant for nano-sol combined spray coating, and a preparation method and application thereof.
[0004] According to a first aspect of the present invention, there is provided an alkali-free liquid flocculant for a nanosol-bonded spray coating, which is prepared from the following raw materials in mass fractions: 5 to 20 parts of magnesium chloride, 5 to 40 parts of magnesium sulfate, 1 to 3 parts of lithium chloride, 0.01 to 0.5 parts of a thickener, 0.1 to 3 parts of a water reducer, and 40 to 80 parts of water.
[0005] Preferably, the nano-sol combined with the alkali-free liquid flocculant for spray coating provided by the present invention is prepared from the following raw materials in mass fraction: 10 to 15 parts of magnesium chloride, 10 to 20 parts of magnesium sulfate, 1 to 2 parts of lithium chloride, 0.05 to 0.1 parts of thickener, 0.5 to 1.5 parts of water reducer, and 55 to 75 parts of water. Under this preferred component ratio, the rebound rate of the spray material is lower (less than 4.0%), and the mechanical strength of the material after hardening is higher.
[0006] In a specific case, the magnesium chloride is magnesium chloride hexahydrate, and the magnesium sulfate is magnesium sulfate heptahydrate.
[0007] Preferably, the thickener is sodium carboxymethyl cellulose.
[0008] Preferably, the water reducer is an aminosulfonate water reducer.
[0009] In a specific case, the nano sol is silica sol.
[0010] According to a second aspect of the present invention, there is provided a method for preparing the nanosol combined with an alkali-free liquid flocculant for spray coating according to the first aspect of the present invention, comprising the following steps:
[0011] (1) Weigh magnesium chloride, lithium chloride, magnesium sulfate and water in proportion, add the four raw materials into a container, and stir for the first time using a stirring device to obtain solution A;
[0012] (2) Weigh the water reducing agent in proportion, add it to solution A, and stir it for the second time using a stirring device to obtain solution B;
[0013] (3) Weigh the thickener in proportion, add it into solution B, and stir it for the third time using a stirring device to obtain the nano-sol combined with the alkali-free liquid flocculant for the spray coating.
[0014] Preferably, the stirring device used in each step is a variable-section spiral arc paddle stirring device.
[0015] Specifically, the first stirring speed is 30 to 60 rpm, and the stirring time is 20 to 50 minutes.
[0016] In specific cases, the second stirring speed is 50-100 rpm and the stirring time is 10-20 minutes.
[0017] In specific cases, the third stirring speed is 50-100 rpm, and the stirring time is 10-20 minutes.
[0018] According to a third aspect of the present invention, there is provided a use of the nanosol combined with the alkali-free liquid flocculant for spray coating according to the first aspect of the present invention in the repair of the inner lining of an iron-making blast furnace.
[0019] The present invention provides a novel alkali-free liquid flocculant for nano-sol-bonded spray coatings. The flocculant is mainly composed of inexpensive magnesium chloride and magnesium sulfate. Magnesium chloride plays a certain role in improving the initial strength of sol-bonded amorphous refractory materials, and its solubility is relatively large and its dissolution rate is also fast. However, concentrated dissolution will generate a large amount of heat, which poses a safety hazard during production. Although magnesium sulfate does not generate heat when dissolved, its solubility is relatively low and its dissolution rate is also relatively slow. When the two are compounded, the amount of magnesium chloride added can be appropriately reduced, which can reduce the heat of dissolution and ensure production safety, and promote the dissolution rate of the two. The lithium chloride introduced in the present invention can promote the gelation of silica sol on the one hand, and the lithium ions decomposed after its dissolution can also promote the hardening of cement, thereby improving the early strength of the spray coating. This is because pure calcium aluminate cement is often introduced into sol-bonded amorphous refractory materials as a hardening accelerator. The Mg introduced by the flocculant 2+ At the same time, the composite thickening substance promotes the rapid flocculation of the nano sol. The sol with added flocculant combined with the excellent plasticity and viscosity of the wet spray material can adhere to the iron plate without any anchoring, with a low rebound rate. The lining formed after spraying is dense and uniform. Moreover, since the flocculant is a human-friendly solution with a pH value between 5 and 6, it avoids the problem of skin burns caused by traditional strong alkaline flocculants, and can achieve a balance between spraying effect and worker safety.
[0020] The alkali-free liquid flocculant for the nano-sol combined spray coating provided by the present invention has the advantages of small addition amount, short flocculation time, fast hardening, etc., and has a significant effect on improving the spraying efficiency of the sol combined wet spray coating and reducing the rebound rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a photo of the nano-sol combined with the alkali-free liquid flocculant for spray coating prepared by the present invention being applied to a repaired iron-making blast furnace. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in this solution will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments.
[0023] If no specific technology or conditions are specified in the embodiments of the present invention, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the devices, instruments, reagents, etc. is not specified, they are all conventional products that can be purchased through regular channels. The raw materials used in the present invention can be easily purchased in the domestic product market.
[0024] In each embodiment and comparative example of the present invention, the magnesium chloride used is industrial magnesium chloride, and the specific indicators must meet the requirements of QB / T2605-2003, and the color is white or off-white, in fragments or granules, and no large blocks are allowed; the magnesium sulfate used is industrial magnesium sulfate, and the specific indicators must meet the requirements of HG / T 2680-2017, and the color is white needle-shaped or oblique columnar crystals, in granules, and no large blocks or large sheets are allowed. The lithium chloride used is industrial lithium chloride, and its specific indicators must comply with the requirements of GB / T10575-2007. It is white in appearance and must not have obvious inclusions. The aminosulfonate water reducer used is a commercially available yellow-brown powder that is easily soluble in water. The sodium carboxymethyl cellulose used is a commercially available industrial product, and its indicators must comply with the requirements of GB / T 12028-2006, and it is a white powdery substance. The water used is tap water. The spray coating TDSP-65 used is a sol-combined wet spray coating product produced by Beijing Jinyutongda Refractory Technology Co., Ltd., and its Al2O3≥65%, SiC≥9%.
[0025] In each embodiment and comparative example of the present invention, the basic process of forming and heat treating the spray coating sample is as follows: first weigh an appropriate amount of spray coating and place it in a stirring pot, add an appropriate amount of silica sol while stirring, stir for 1 to 2 minutes to form a self-flowing state, quickly add an appropriate amount of flocculant, and then stir for 3 to 5 seconds, quickly take out the stirred spray coating, take an appropriate amount and place it in the mold, after fully ramming and smoothing the surface, put it in a natural environment (10°C to 30°C) for curing, and after curing for 24 hours, demould the sample and place it in a 110°C constant temperature oven for treatment, take it out after 24 hours, and then place the baked sample in an electric furnace according to the standard requirements. The volume density, room temperature flexural strength and room temperature compressive strength of the sample are tested in accordance with the relevant standard requirements for the determination of physical properties of amorphous refractory materials in Part VI of GB / T 4513.6.
[0026] The detection method of the rebound rate of spray paint is as follows: place 1 ton of spray paint in a mixer, add an appropriate amount of silica sol while stirring, stir for 1 to 2 minutes until it becomes a self-flowing state, put it into the hopper of a pumping machine, then start the flocculant pump, turn on the high-pressure air switch, start the pumping machine, and spray the mixed spray paint onto the iron plate through a spray gun. After the spraying is completed, weigh the weight M1 of the rebound material and weigh the weight M2 of the material on the iron plate. The rebound rate f is calculated as: f=M1 / (M1+M2)×100%.
[0027] Embodiment 1:
[0028] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight: 10 parts of magnesium chloride hexahydrate, 20 parts of magnesium sulfate heptahydrate, 1 part of lithium chloride, 0.1 parts of sodium carboxymethyl cellulose, 0.5 parts of aminosulfonate water reducer, and 68.4 parts of water;
[0029] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0030] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 10.6%, and the flocculant addition amount was 0.8%. After adding, the spray coating flocculated within 5 seconds, the adhesion effect of the sprayed material was good, and the rebound rate was measured to be 3.7%. The volume density of the spray coating sample at 110℃×24h was 2.46g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 7.9MPa, and the compressive strength is 77.3MPa; the flexural strength of the spray coating sample at 1400℃×3h is 16.5MPa, and the compressive strength is 104.9MPa.
[0031] Embodiment 2:
[0032] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight: 15 parts of magnesium chloride hexahydrate, 20 parts of magnesium sulfate heptahydrate, 1 part of lithium chloride, 0.1 parts of sodium carboxymethyl cellulose, 1 part of aminosulfonate water reducer, and 70.2 parts of water;
[0033] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0034] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 10.6%, and the flocculant addition amount was 0.8%. After adding, the spray coating flocculated within 5 seconds, the adhesion effect of the sprayed material was good, and the rebound rate was measured to be 3.5%. The volume density of the spray coating sample at 110℃×24h was 2.48g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 7.5MPa, and the compressive strength is 77.6MPa; the flexural strength of the spray coating sample at 1400℃×3h is 18.5MPa, and the compressive strength is 102.3MPa.
[0035] Embodiment 3:
[0036] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight: 12 parts of magnesium chloride hexahydrate, 15 parts of magnesium sulfate heptahydrate, 1.5 parts of lithium chloride, 0.1 parts of sodium carboxymethyl cellulose, 0.5 parts of aminosulfonate water reducer, and 55 parts of water;
[0037] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0038] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 10.6%, and the flocculant addition amount was 0.8%. After adding, the spray coating flocculated within 5 seconds, the adhesion effect of the sprayed material was good, and the rebound rate was measured to be 3.9%. The volume density of the spray coating sample at 110℃×24h was 2.51g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 7.7MPa, and the compressive strength is 71.8MPa; the flexural strength of the spray coating sample at 1400℃×3h is 19.7MPa, and the compressive strength is 105.4MPa.
[0039] Embodiment 4:
[0040] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight: 15 parts of magnesium chloride hexahydrate, 25 parts of magnesium sulfate heptahydrate, 1 part of lithium chloride, 0.1 parts of sodium carboxymethyl cellulose, 0.5 parts of aminosulfonate water reducer, and 58.4 parts of water;
[0041] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0042] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 10.6%, and the flocculant addition amount was 0.8%. After adding, the spray coating flocculated within 5 seconds, the adhesion effect of the sprayed material was good, and the rebound rate was measured to be 4.2%. The volume density of the spray coating sample at 110℃×24h was 2.47g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 6.7MPa, and the compressive strength is 58.4MPa; the flexural strength of the spray coating sample at 1400℃×3h is 15.9MPa, and the compressive strength is 86.7MPa.
[0043] Embodiment 5:
[0044] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight as follows: 5 parts of magnesium chloride hexahydrate, 30 parts of magnesium sulfate heptahydrate, 2 parts of lithium chloride, 0.2 parts of sodium carboxymethyl cellulose, 1 part of aminosulfonate water reducer, and 63.3 parts of water;
[0045] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0046] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 11.0%, and the flocculant addition amount was 0.9%. After adding, the spray coating flocculated within 5 seconds, the adhesion effect of the sprayed material was good, and the rebound rate was measured to be 4.1%. The volume density of the spray coating sample at 110℃×24h was 2.45g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 6.2MPa, and the compressive strength is 63.9MPa; the flexural strength of the spray coating sample at 1400℃×3h is 14.5MPa, and the compressive strength is 95.7MPa.
[0047] Embodiment 6:
[0048] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight as follows: 8 parts of magnesium chloride hexahydrate, 32 parts of magnesium sulfate heptahydrate, 2.5 parts of lithium chloride, 0.25 parts of sodium carboxymethyl cellulose, 1.2 parts of aminosulfonate water reducer, and 56.05 parts of water;
[0049] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0050] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 10.6%, and the flocculant addition amount was 0.7%. After adding, the spray coating flocculated within 5 seconds, the adhesion effect of the sprayed material was good, and the rebound rate was measured to be 4.7%. The volume density of the spray coating sample at 110℃×24h was 2.47g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 6.3MPa, and the compressive strength is 67.3MPa; the flexural strength of the spray coating sample at 1400℃×3h is 13.9MPa, and the compressive strength is 95.9MPa.
[0051] Comparative Example 1:
[0052] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight as follows: 25 parts of magnesium chloride hexahydrate, 45 parts of magnesium sulfate heptahydrate, 1 part of lithium chloride, 0.1 part of sodium carboxymethyl cellulose, 0.5 part of aminosulfonate water reducer, and 28.4 parts of water;
[0053] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0054] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 10.6%, and the flocculant addition amount was 0.8%. After adding, the spray coating flocculated within 3 seconds, and the adhesion effect of the sprayed material was poor. The rebound rate was measured to be 20.9%. The volume density of the spray coating sample at 110℃×24h was 2.45g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 4.1MPa, and the compressive strength is 21.6MPa; the flexural strength of the spray coating sample at 1400℃×3h is 11.3MPa, and the compressive strength is 76.1MPa.
[0055] Comparative Example 2:
[0056] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight as follows: 3 parts of magnesium chloride hexahydrate, 2 parts of magnesium sulfate heptahydrate, 1 part of lithium chloride, 0.05 parts of sodium carboxymethyl cellulose, 1 part of aminosulfonate water reducer, and 92.95 parts of water;
[0057] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0058] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 10.8%, and the flocculant addition amount was 0.8%. After adding, the spray coating flocculated within 10 seconds. The adhesion effect of the sprayed material was poor, and there was a small amount of flowing phenomenon. The measured rebound rate was 27.9%, and the volume density of the spray coating sample at 110℃×24h was 2.42g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 3.9MPa, and the compressive strength is 24.3MPa; the flexural strength of the spray coating sample at 1400℃×3h is 9.7MPa, and the compressive strength is 71.3MPa.
[0059] Comparative Example 3:
[0060] a. The alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention is expressed by weight: 10 parts of magnesium chloride hexahydrate, 15 parts of magnesium sulfate heptahydrate, 0.5 parts of lithium chloride, 1 part of sodium carboxymethyl cellulose, 1 part of aminosulfonate water reducer, and 72.5 parts of water;
[0061] b. Weigh magnesium chloride hexahydrate, lithium chloride, magnesium sulfate heptahydrate and water according to the above proportions, put the four raw materials into a stainless steel barrel, and stir them with a variable-section spiral arc paddle stirring device at a speed of 60 rev / min for 50 minutes to obtain solution A; weigh aminosulfonate water reducer according to the proportion, put it into solution A, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain solution B; weigh sodium carboxymethyl cellulose according to the proportion, put it into solution B, and stir it with a variable-section spiral arc paddle stirring device at a speed of 100 rev / min for 20 minutes to obtain the nanosol combined with an alkali-free liquid flocculant for a spray coating;
[0062] c. The above-mentioned alkali-free liquid flocculant was applied to the nano-sol combined wet spray coating TDSP-65 of Beijing Jinyutongda Refractory Technology Co., Ltd. The silica sol used was 30 silica sol, the sol addition amount was 11.0%, and the flocculant addition amount was 1.2%. After adding, the spray coating flocculated within 5 seconds, and the adhesion effect of the sprayed material was slightly poor. The rebound rate was measured to be 15.1%. The volume density of the spray coating sample at 110℃×24h was 2.43g / cm 3 The flexural strength of the spray coating sample at 110℃×24h is 6.1MPa, and the compressive strength is 62.5MPa; the flexural strength of the spray coating sample at 1400℃×3h is 11.4MPa, and the compressive strength is 87.1MPa.
[0063] Application examples:
[0064] The nano-sol prepared in Example 1 of the present invention in combination with the alkali-free liquid flocculant for spray coating was applied to the repair of a certain iron-making blast furnace.
[0065] During construction, the crane will first lift the ton-packaged spray paint to the top of the mixer. Under the action of several sharp blades above the mixer and the gravity of the ton-package, the material is placed into the mixer in about 30 seconds, and then an appropriate amount of nanosol is added. After 2 minutes of stirring, the self-flowing material is placed into the hopper of the pumping equipment and transported to the furnace under high pressure. Near the end of the spray gun head, the material and flocculant are quickly mixed under the action of high-pressure air, causing the self-flowing material to instantly lose fluidity and become plastic and viscous. Finally, it is sprayed onto the work surface by the sprayer.
[0066] See attached for photos of the blast furnace interior after construction is completed Figure 1 The actual production application further confirmed that the alkali-free liquid flocculant for the nano-sol combined spray coating of the present invention has the advantages of small addition amount, short flocculation time, fast hardening, etc., and has a significant effect on improving the spraying efficiency of the sol combined wet spray coating and reducing the rebound rate.
[0067] The above embodiments are only used to illustrate rather than limit the technical solutions of the present invention. Although the above embodiments describe the present invention in detail, relevant technical personnel in the field should understand that the present invention can be modified or equivalently replaced, but any modification and partial replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. An alkali-free liquid flocculant for a nano-sol combined spray coating, characterized in that: The nano-sol is prepared from the following raw materials in mass fractions: 5 to 20 parts of magnesium chloride, 5 to 40 parts of magnesium sulfate, 1 to 3 parts of lithium chloride, 0.01 to 0.5 parts of thickener, 0.1 to 3 parts of water reducer, and 40 to 80 parts of water; the nano-sol is silica sol, and the spray coating is an amorphous refractory material for repairing the lining of an iron-making blast furnace.
2. The alkali-free liquid flocculant for nano-sol combined spray coating according to claim 1, characterized in that: The magnesium chloride is magnesium chloride hexahydrate, and the magnesium sulfate is magnesium sulfate heptahydrate.
3. The alkali-free liquid flocculant for nano-sol combined spray coating according to claim 1, characterized in that: The thickener is sodium carboxymethyl cellulose.
4. The alkali-free liquid flocculant for nano-sol combined spray coating according to claim 1, characterized in that: The water reducer is an aminosulfonate water reducer.
5. A method for preparing the nano-sol combined with an alkali-free liquid flocculant for spray coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Weigh magnesium chloride, lithium chloride, magnesium sulfate and water in proportion, add the four raw materials into a container, and stir for the first time using a stirring device to obtain solution A; (2) Weigh the water reducing agent in proportion, add it to solution A, and stir it for the second time using a stirring device to obtain solution B; (3) Weigh the thickener according to the proportion, put it into solution B, and stir it for the third time using a stirring device to obtain the nanosol combined with the alkali-free liquid flocculant for the spray coating.
6. The preparation method according to claim 5, characterized in that: The first stirring speed is 30-60 rpm, and the stirring time is 20-50 minutes.
7. The preparation method according to claim 5, characterized in that: The second stirring speed is 50-100 rpm, and the stirring time is 10-20 minutes.
8. The preparation method according to claim 5, characterized in that: The third stirring speed is 50-100 rpm, and the stirring time is 10-20 minutes.
9. Use of the nano-sol combined with the alkali-free liquid flocculant for spray coating according to any one of claims 1 to 4 in the repair of the inner lining of an iron-making blast furnace.
Citation Information
Patent Citations
Fluorine-free liquid alkali-free accelerator as well as preparation method and application thereof
CN113087441A